Relative clause sentence comprehension by rioplatense spanish-speaking children aged 6-11 years - Zamora, Dolores (2023)
Relative clause comprehension has been the object of numerous investigations in children, but few have been able to establish the stage in which it is acquired, and research in Spanish is scarce. The aim of this study is to compare the performance of Rioplatense Spanish-speaking children in the comprehension of relative clauses. For that purpose, a total of 105 children from three age groups: 6-7, 8-9, and 10-11 years old, respectively, were assessed with an oral comprehension task of subject and object relative clauses. Results show significant differences in the performance of each group. Children of all ages have difficulty understanding object relative clauses, while performance in subject relative clauses depends on the position of the subordinate clause.